Exploring exclusive breastfeeding readiness: experiences of first-time mothers in Lusaka, Zambia - Francis Sichimba; Kalunga Cindy Nakazwe; Lena Halawi; Atika Khalaf (International Journal of Qualitative Studies on Health & Well-Being)
Background The World Health Organization recommends exclusive breastfeeding for the first six months of a baby’s life. While many studies have provided insight into exclusive breastfeeding in Zambia, few have looked at the experiences of first-time mothers and exclusive breastfeeding readiness. Objective To explore exclusive breastfeeding readiness and experiences of first-time mothers in Zambia. Methods A qualitative descriptive study employing a phenomenological design was conducted with 17 mothers. Data was collected using a semi-structured face-to-face interview guide. Thematic analysis was used to analyse the interview transcripts. Results The analysis resulted in an overarching theme: Breastfeeding Readiness—A Multifaceted Approach with four categories: Exclusive Breastfeeding Readiness and Motivation, Support Networks in the Breastfeeding Journey, Navigating the Exclusive Breastfeeding Journey, and Perceived Resources to Support Exclusive Breastfeeding Readiness. Conclusions Based on the findings, it is evident that although first-time mothers have knowledge on exclusive breastfeeding, mentally and practically, they are not ready to do so successfully. The study recommends improved prenatal and postnatal care provided to new mothers, with a focus on mental health readiness, breastfeeding instruction, and skills development.